(untitled) (American & British Studies Annual, 2014)
This paper discusses the film The Boy with Green Hair (1948), directed by Joseph Losey. It focuses on the film’s representation of the war orphan not only as a sorrowing child, but also as someone who has been marked as exceptional in order to raise public awareness on issues of war and racial injustice in the immediate postwar period. Among the sources used are reviews and critiques of the film at the time of its release in 1948; interviews with and memoirs of key personnel at RKO Radio Pictures, as well as Losey; and analyses of the film’s changing reputation. Initially viewed by some as Communist propaganda, The Boy with Green Hair is now admired as a film that boldly promoted international peace at a time when the Cold War was heating up.